IGlarLixi versus basal plus Rapid‐Acting insulin in adults with type 2 diabetes advancing from basal insulin therapy: The SoliSimplify Real‐World study. Issue 1 (19th September 2022) - McCrimmon, Rory J.; Cheng, Alice Y.Y.; Galstyan, Gagik; Djaballah, Khier; Li, Xuan; Coudert, Mathieu; Frias, Juan P.
Abstract: Aim: For people with suboptimally controlled type 2 diabetes (T2D) on basal insulin (BI), guidelines recommend several treatment advancement options. This study compared the clinical effectiveness of once‐daily iGlarLixi versus a multiple‐injection BI + rapid acting insulin (RAI) regimen in adults with T2D advancing from BI therapy in real‐world clinical practice. Materials and methods: Electronic medical records from the Observational Medical Outcomes Partnership (OMOP) database were analysed retrospectively using propensity score matching to compare therapy advancement with iGlarLixi or BI + RAI in US adults ≥18 years with T2D on BI who had ≥1 valid glycated haemoglobin (HbA1c) value at baseline and at the 6‐month follow‐up. The primary objective was non‐inferiority of iGlarLixi to BI + RAI in HbA1c change from baseline to 6 months (margin 0.3%). Results: Propensity score matching generated cohorts with balanced baseline characteristics (N = 814 in each group). HbA1c reduction from baseline to 6 months with iGlarLixi was non‐inferior to BI + RAI [mean difference (95% confidence interval): 0.1 (−0.1, 0.2)%; one‐sided p = .0032]. At 6 months, weight gain was significantly lower with iGlarLixi than with BI + RAI [−0.8 (−1.3, −0.2) kg; two‐sided p = .0069]. Achievement of HbA1c <7% without hypoglycaemia and weight gain were similar between groups [odds ratio (95% confidence interval): 1.15 (0.81, 1.63); p = .4280]. Hypoglycaemia was low in both groups, probably because of underreporting. Conclusions: In real‐world clinical practice, glycaemic outcomes 6 months after treatment advancement from BI are similar for people with T2D using iGlarLixi versus BI + RAI, with iGlarLixi leading to less weight gain.